Effect of Management Control System on Employee Performance at PT. Sigma Poly Internusa During Covid-19 - Mosa Aprilriyan Tjipta; Maria Natalia (SINTESA, 2022)
The Covid-19 pandemic has a negative impact on a country’s economy. Therefore, every company is required to carry out its business activities in a more professional. In carrying out its business activities, a management control system is needed to be able to regulate and evaluate every company policy in achieving their goals. This study aims to analyze "The Influence of Management Control Systems on Employee Performance at PT. Sigma Poly Internusa Bandung City. This research is a quantitative research methods with an explanatory approach with a sample of 75 respondents employees of PT. Sigma Poly Internusa Bandung City The data collection technique in this study used a questionnaires, while the techniques used to analyze are: validity test, uni reliability, simple regression test, hypothesis testing. The results in this study indicate that the Management Control System has a positive and significant effect on employee performance.